Synthesis and evaluation of arylimino pyridine nickel(II) catalysts: influence of substituents оn polyethylene structure - Rocha, L.; Ferreira, L.; Marques, M. (Publishing House of Lviv Polytechnic National University, 2015)
The asymmetric arylimino pyridine Ni(II) catalysts have been examined with different substituents including diisopropyl, diethyl, fluoro, and chloro groups.The influence of these substituents and variation of ethylene pressure on the catalytic activity, crystalline structure, as well as on thermal properties of polyethylene has been investigated. The result show that complexes with substituent alkyl groups, which provide the increased electron density on the metal center (o-diethyl and o-diisopropyl) exhibit higher activity, compared to those with electron acceptors substituents (o-fluoro and o-chloro). Досліджені асиметричні ариліміно піридин Ni(II) каталізатори з різними замісниками, включаючи диізопропіл-діетил-, флуоро- і хлор-замісники. Досліджено вплив цих замісників і тиску етилену на каталітичну активність, кристалічну структуру, і термічні властивості поліетилену. Показано, що комплекси із заміщеними алкільними групами, які забезпечують підвищену електронну щільність на центрі металу (о-діетил і о-діізопропіл), більш активні в порівнянні з комплексами з електрон-акцепторними замісниками (о-флуоро і о-хлор).
Синтез і характеристика нікель(II) ариліміно піридинових каталізаторів: Вплив замісників на структуру поліетилену
Keywords: homogeneous catalyst; ethylene polymerization; asymmetric catalyst; гомогенний каталізатор; полімеризація етилену; асиметричний каталізатор